Successful without sex: the enigmatic biology and evolutionary origin of coralroot bittercress (Cardamine bulbifera, Brassicaceae) - Ru, Yalu; Schulz, Rainer; Koch, Marcus (Perspectives in plant ecology, evolution and systematics, 2020)
Cardamine bulbifera (Coralroot Bittercress) is one of the Central European enigmatic plant species. Although the species is wide-spread all over Europe, no reproduction via seeds has ever been observed. Instead dispersal of vegetative leaf-axillary bulbs assures effective propagation. In our study we analyzed different life stages and factors affecting sexual reproduction and seek for unravelling the evolutionary origin of this polyploid species. We combined studies on pollen quality and fertility, pollen-stigma interactions, growth performance, and reproductive success with common garden experiments, controlled pollination and genotyping analysis (AFLPs). We also tested the interplay of resource allocation either into developing fruits and seeds or into reproductive organs generated by vegetative means. Cytogenetic analyses were conducted addressing variation in chromosome numbers and ploidy level. Phylogenetic relationships among possible parental lineages of Eurasian Cardamine species were reconstructed based on whole plastome sequences and the entire nuclear encoded rDNA cistron. We have shown herein that sexual reproduction of Cardamine bulbifera is hindered at various stages of reproductive development. We did not find any complete interruption of reproductive development except final embryo arrest. We detected low pollen germination rates and slow pollen tube growth. Less than 25 % of flowers matured into siliques with most often low-quality seeds; only 2% of those seeds developed towards early stages of germination but arrested before primary root formation. Results are independent from genotypes or vegetative propagation. Phylogenetic data demonstrate close relationships to C. quinquefolia and C. abchasica, but don’t indicate a hybrid origin involving distant species from other lineages. Cardamine bulbifera is a fully functional sexual plant with attractive flowers, nectar production, viable pollen, functional ovules and no signatures of a sporophytic incompatibility system. Highly reduced seed set and failure in seedling formation may be causally linked to a polyploid origin in the Caucasus region. Long-term survival has been achieved by rapid transition towards vegetative propagation and subsequent range expansion.
Gesehen am 17.11.2020